Estimating retrospective exposure of household humidifier disinfectants. (21st January 2015) - Park, D. U.; Friesen, M. C.; Roh, H. S.; Choi, Y. Y.; Ahn, J. J.; Lim, H. K.; Kim, S. K.; Koh, D. H.; Jung, H. J.; Lee, J. H.; Cheong, H. K.; Lim, S. Y.; et al.
Abstract: We conducted a comprehensive humidifier disinfectant exposure characterization for 374 subjects with lung disease who presumed their disease was related to humidifier disinfectant use (patient group) and for 303 of their family members (family group) for an ongoing epidemiological study. We visited the homes of the registered patients to investigate disinfectant use characteristics. Probability of exposure to disinfectants was determined from the questionnaire and supporting evidence from photographs demonstrating the use of humidifier disinfectant, disinfectant purchase receipts, any residual disinfectant, and the consistency of their statements. Exposure duration was estimated as cumulative disinfectant use hours from the questionnaire. Airborne disinfectant exposure intensity ( μ g/m 3 ) was estimated based on the disinfectant volume (ml) and frequency added to the humidifier per day, disinfectant bulk level ( μ g/ml), the volume of the room (m 3 ) with humidifier disinfectant, and the degree of ventilation. Overall, the distribution patterns of the intensity, duration, and cumulative exposure to humidifier disinfectants for the patient group were higher than those of the family group, especially for pregnant women and patients ≤6 years old. Further study is underway to evaluate the association between the disinfectant exposures estimated here with clinically diagnosed lung disease.